Jane Austen speaks Norwegian : the challenges of literary translation - Sørbø, Marie N. (Costerus, 2018)
What can translations reveal about the global reception of any authorship? In Jane Austen Speaks Norwegian: The Challenges of Literary Translation, Marie Nedregotten Sørbø compares two novels and six translations of them. The discussion is entirely in English, as all Norwegian versions are back-translated. This study therefore lends itself to comparisons with other languages, and aims to fill its place as one component in a worldwide field of research; how Jane Austen is understood and transmitted. Moreover, this book presents a selection of pertinent issues for any translator, including abbreviation and elaboration, style and vocabulary, and censorship. Sørbø gives vivid examples of how literary translation happens, and how it serves to interpret and refashion literature for new readerships.